2006
DOI: 10.1534/genetics.105.048223
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Bayesian Inference Reveals Evidence for a Recent, Severe Bottleneck in a Netherlands Population of Drosophila melanogaster

Abstract: Genome-wide nucleotide variation in non-African populations of Drosophila melanogaster is a subset of variation found in East sub-Saharan African populations, suggesting a bottleneck in the history of the former. We implement an approximate Bayesian approach to infer the timing, duration, and severity of this putative bottleneck and ask whether this inferred model is sufficient to account for patterns of variability observed at 115 loci scattered across the X chromosome. We estimate a recent bottleneck 0.006N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
351
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(380 citation statements)
references
References 47 publications
27
351
2
Order By: Relevance
“…It is therefore reasonable to assume that positive selection could have a substantial confounding effect on a variety of population genomic methods for demographic inference in practice, beyond those considered here. In the empirical literature, numerous recent studies of demographic history have found support for contractions and recent expansions of natural populations (Thornton and Andolfatto 2006;Fagundes et al 2007;Gravel et al 2011;Tennessen et al 2012;Duchen et al 2013). While such population size changes are probably common, and our results do not call the major findings of these studies into question, they do suggest that natural selection can exaggerate the inferred intensity of these changes.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…It is therefore reasonable to assume that positive selection could have a substantial confounding effect on a variety of population genomic methods for demographic inference in practice, beyond those considered here. In the empirical literature, numerous recent studies of demographic history have found support for contractions and recent expansions of natural populations (Thornton and Andolfatto 2006;Fagundes et al 2007;Gravel et al 2011;Tennessen et al 2012;Duchen et al 2013). While such population size changes are probably common, and our results do not call the major findings of these studies into question, they do suggest that natural selection can exaggerate the inferred intensity of these changes.…”
Section: Discussioncontrasting
confidence: 48%
“…Recent studies of large population samples capable of observing very rare alleles found evidence that this growth has accelerated dramatically within the last several thousand years (Coventry et al 2010;Tennessen et al 2012;Gao and Keinan 2016). Similarly, recent studies in Drosophila melanogaster show evidence of a severe out-of-Africa bottleneck (Begun and Aquadro 1993), but occurring within the last 20,000 years (Li and Stephan 2006;Thornton and Andolfatto 2006).While demographic inference from population genomic data in its various forms has proven to be a successful technique, a unifying assumption of these various inference methods (ABC, SFS-based, and SMC-based approaches) is that the genetic data in question are strictly neutral and free from the effects of linked selection in the genome. While this is an important simplifying assumption, it may be the case that in many populations a sizeable fraction of the genome is influenced by natural selection (Hahn 2008;Sella et al 2009;Corbett-Detig et al 2015).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This model has five parameters: the population mutation rate (u ¼ 4N 0 m, where N 0 is the effective size of the ancestral population), the population recombination rate (r ¼ 4N 0 r), the time at which the derived population recovered from the bottleneck (t r ), the duration of the bottleneck (d), and the severity of the bottleneck ( f, 0 , f # 1). In this study, we use u ¼ 0.01/site, r ¼ 0.1/site, t r ¼ 0.004, d ¼ 0.015, and f ¼ 0.03, as these bottleneck parameters are compatible with data from European samples of D. melanogaster (Thornton and Andolfatto 2006). To perform these simulations, a program was written using the coalescent simulation functions in libsequence (Thornton 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial mutation fixed in the recent past at t ¼ 0.0041 or 0.015, and we examined two strengths of selection-a ¼ 2fN 0 s ¼ 100 or a ¼ 1500. We assume N 0 ¼ 2.4 million (Thornton and Andolfatto 2006), and therefore our values of a correspond to s % 7 3 10 À4 and % 0.01, respectively. We are therefore studying the effect of a recent and relatively strong (2fN 0 s?1) sweep occurring at all loci in the history of the derived population.…”
Section: Methodsmentioning
confidence: 99%